Prevalence and factors associated with arterial hypertension in people who live at altitude - Diaz-Lazo, Anibal (2025)
Objective: to determine the prevalence and factors associated with high blood pressure (HTN) in adults who live at high altitude. Material and methods: observational, analytical, cross-sectional and prospective study. A sample of 843 people aged 18 or older was included; HBP was defined as a blood pressure value ≥ 140/90 mmHg. A survey was carried out using simple random sampling. Adjusted prevalence rates were estimated to determine associated factors. P< 0,05 was shown to be significant. Results: the median age was 53 years (IQR: 27); 520 (61,7%) were women; 307 (36,4%) were > 60 years old. A prevalence of HTN was found to be 19,6% (165). Between 40 and 49 years of age the prevalence was 14% and from 70 and older it was 41%. The incidence of new cases was 8,30 cases per 1000 people, 71,5% (118) received pharmacological treatment, of which 72,8% (86) were on monotherapy. HBP control was 70,9% (117). The factors positively associated with HTN were alcohol consumption (PR=1,65; 95%CI=1,09-2,49) and negatively associated with diabetes mellitus (PR=0,43;95%CI=0,30-0,61) and obesity (PR=0,69;95%CI=0,49-0,96) according to the multivariate analysis carried out adjusted for age and sex. Conclusion: the prevalence of HTN is high, which increases with increasing age and the factor favorably associated with HTN was alcohol consumption, while diabetes mellitus and obesity were negatively associated.